The Montessori Bibliography Online: A Resource for the Global Montessori Community - Parham, Joel (Journal of Montessori Research, 2022)
The Montessori Bibliography Online (MBO) makes information about Montessori education and the Montessori movement more accessible through an online interface that includes links to digitized source materials. Historically, Montessori bibliographies and indexes have been published in physical form and include references to other sources, but a direct link is absent. This database builds on previously compiled indexes to consolidate citations into a comprehensive repository with an intuitive user interface and a robust search capability. Additionally, the MBO provides hyperlinks to digitized source material. Although this type of tool is not unprecedented in the larger research and educational landscape, it is novel within the domain of Montessori education. This methodological essay discusses the steps I took to compile and develop the MBO. Beginning with a review of the literature and legal matters, the discussion describes the methods and processes employed. It concludes by outlining future directions for the MBO. The MBO is accessible at https://montessoribib.ku.edu.